Pengembangan E-LKPD Interaktif Menggunakan Liveworksheet Berbasis Model Problem Based Learning (PBL) Pada Pembelajaran Keberagaman Budaya Kelas V Di Sekolah Dasar - Diana, Putri; Masniladevi, Masniladevi; Ladiva, Hasmai Bungsu; Fitria, Yanti (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The background of the research arises from observations and interviews at SDN 13 Surau Gadang, SDN 24 Ujung Gurun, and SDN 20 Berok Gunung Pangilun which show a low use of electronic LKPD, thus impacting the decline in enthusiasm and active learning of students. This study aims to develop an interactive E-LKPD using liveworksheet based on the Problem Based Learning (PBL) model in the cultural diversity learning for fifth grade in elementary school. The research employs the Research & Development method with the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The data collected includes validity and practicality. The validation results show a percentage of 90% (very valid) from material experts, 81.8% (very valid) from media experts, and 95% (very valid) from language experts. The practicality test resulted in a percentage of 96.4% (very practical) from teachers and 96% (very practical) from students. It can be concluded that the developed interactive E-LKPD has been proven to be valid and practical to support the learning process of Pancasila Education in fifth-grade elementary school.